2016
DOI: 10.1097/md.0000000000003704
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Standard Oral Nutrition Supplements Versus Immunonutrition in Patients Undergoing Colorectal Resection in an Enhanced Recovery (ERAS) Protocol

Abstract: To compare immunonutrition versus standard high calorie nutrition in patients undergoing elective colorectal resection within an Enhanced Recovery After Surgery (ERAS) program.Despite progress in recent years in the surgical management of patients with colorectal cancer (ERAS programs), postoperative complications are frequent. Nutritional supplements enriched with immunonutrients have recently been introduced into clinical practice. However, the extent to which the combination of ERAS protocols and immunonutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
1
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 35 publications
(28 reference statements)
5
104
1
16
Order By: Relevance
“…Although some studies showed no significant difference with hospital stay in immunonutrition group [33, 36], different outcome was observed in our study. We attribute the result to the choice of the subjects.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Although some studies showed no significant difference with hospital stay in immunonutrition group [33, 36], different outcome was observed in our study. We attribute the result to the choice of the subjects.…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, Rowan and his collaborators published their results that perioperative immunonutrition may lead to significant reductions of postoperative complications in high-risk head and neck cancer patients [32]. Moreover, Silvestri et al compared the clinical characteristics of patients after pancreaticoduodenectomy between immunonutrition group and control group and then obtained the result that immunonutrition helps to lower the risk of postoperative infectious complications and of hospital stays [3335]. In our cohort, we obtained similar results with patients of thymoma with MG; the morbidity of postoperative complications, especially infectious complications, was significantly reduced in IN group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger was a RCT of 264 patients that demonstrated a reduction in infectious complications (23.8% vs 10.7%; P = .0007), particularly wound infections (16.4% vs 5.7%; P = .0008) with the use of IMN when compared to standard high-calorie supplements. 82 In a separate study of IMN compared to dietary advice without supplementation by the same authors, wound infection rates in laparoscopic colectomy were significantly reduced with the use of IMN (11.5% vs 0%; P = .006). 83 A major real-world quality improvement effort using preoperative IMN in 3375 patients in Washington state demonstrated a reduction of 23% in the number of patients with a prolonged LOS (P = .05) in a covariate-matched analysis.…”
Section: Role Of Perioperative Imnmentioning
confidence: 99%
“…Although most of the included trials were from gastric/colon surgery, one study in gynecologic oncology supported these results 213. Several large randomized trials in colorectal patients compared an immune nutrition/high protein diet to a high calorie supplement and found a lower rate of infection and length of stay in the immune nutrition group 214. Higher post-operative protein intake is also associated with earlier discharge 215.…”
Section: Resultsmentioning
confidence: 99%